“Against the Source”:: Daphne Marlatt’s Revision of Charles Olson - Reed, Sabrina (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2001)
In order to examine the influence of Charles Olson on Daphne Marlatt it is useful to compare Marlatt's Steveston with Olson's The Maximus Poems. Although Marlatt identifies Olson as one of her mentors, she is also uneasy with his masculine-centred approach. This uneasiness emerges largely from Olson's confidence in the physical body and its ability to claim a space for its poetry and its possessor. Alternately, Marlatt's poems in Steveston often figure the female body and its experiences in problematic terms. Although Steveston and The Maximus Poems are similar in content and style, Marlatt begins a process of questioning just how, in the face of Olson's universal male pronouncements on the body, her own female experience should be presented. Later in her career, particularly in Touch to My Tongue, Marlatt's poetry becomes more grounded in the theories of feminist critics such as Irigaray and Cixous who emphasize the more celebratory aspects of the female body.